2018
DOI: 10.1007/s11356-018-3104-x
|View full text |Cite
|
Sign up to set email alerts
|

Rarasaponin-bentonite-activated biochar from durian shells composite for removal of crystal violet and Cr(VI) from aqueous solution

Abstract: This paper presents the preparation of composite material and its application for the adsorption of crystal violet and Cr(VI) from aqueous solution onto acid-activated bentonite (AAB) and rarasaponin-bentonite-activated biochar from durian shells composite (RBAB). The influence of initial pH of the solution and the temperature of adsorption on the adsorbents adsorption performance was also studied. Langmuir and Freundlich models could represent the adsorption equilibria equally well. Thermodynamic parameters s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Specifically, K F was calculated as 12.56, 16.28 and 17.68 at 10, 25 and 40°C, respectively. Similar results were also reported by other researchers when studying the adsorption performance of the pristine and modified biochars [34,35]. Although similar thermodynamic behaviors were found for the MBC and BC (Table S3), the maximum adsorption capacity of the MBC and BC towards RhB was much lower than that of the AMBC.…”
Section: Rhb Adsorption Isothermssupporting
confidence: 89%
“…Specifically, K F was calculated as 12.56, 16.28 and 17.68 at 10, 25 and 40°C, respectively. Similar results were also reported by other researchers when studying the adsorption performance of the pristine and modified biochars [34,35]. Although similar thermodynamic behaviors were found for the MBC and BC (Table S3), the maximum adsorption capacity of the MBC and BC towards RhB was much lower than that of the AMBC.…”
Section: Rhb Adsorption Isothermssupporting
confidence: 89%
“…One of the most common applications of fruit waste is for the production of bioadsorbents. Laysandra et al [ 113 ] used durian skin to produce adsorbent by mixing it with acid-activated bentonite (AAB) and natural surfactant (rarasaponin). They found that the rarasaponin/bentonite-activated biochar from the durian shell composite (RBAB) was effective for use as a new composite adsorbent for the removal of crystal violet and Cr (VI) from aqueous solutions.…”
Section: By-productsmentioning
confidence: 99%
“…It is a good material for the preparation of biomass adsorbents [ 24 ]. However, most of the common adsorbents prepared from durian shells have the disadvantages of large particle size and difficulty in recycling after adsorption [ 25 , 26 , 27 ]. Moreover, Fe 3 O 4 shows excellent separate characteristics due to its magnetic properties [ 28 ].…”
Section: Introductionmentioning
confidence: 99%